Bridget Jones's diary : a novel - Fielding, Helen, 1958- (Penguin Books, 1999)
A comedy on an Englishwoman's quest for self-improvement. Single and thirty-something Bridget diets, keeps tabs on her tobacco and alcohol consumption, visits the gym regularly, yet she still has problems finding the right man. A debut in fiction. Helen Fielding has stated openly that her bestselling novel is based on Jane Austen's enduring classic, and the character Mark Darcy is, of course, named after Austen's famous Mr. Darcy.